KAMPUNG KARANGKAJEN YOGYAKARTA - S a ti v a, S a ti v a (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
ABSTRACT Kampong Karangkajen Yogyakarta is an old kampong that most native residences are batik enterpreneur. Most of them still have close relationship, evenmore family relationship. So that there is a unique relationship among the residences, especially in their informal relation. The aim of this research is to look for characteristic of informal gathering space at Kampong Karangkajen Yogyakarta, and to get determine factor of the characteristic, through typology study. This research uses rasionalistic-qualitative paradigm. Before analyzing the data, the researcher studied several references, especially about typology in architecture. The study results theory frame that will drive data analyze, that is 9 cases of informal gathering space at Kampong Karangkajen Yogyakarta. The result of this research show that there is a typology of informal gathering space at Kampong Karangkajen Yogyakarta, especially in physical factor that support activity comfortness. The determine factors influenced the typology are: the users, the activities and the time when the activities happened. Keywords: typology, informal gathering space, Kampong Karangkajen Yogyakarta